2020
DOI: 10.1016/j.lfs.2020.117368
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids-induced cardiac protection against ischemia/reperfusion injury

Abstract: Aims: Amino acids, especially branched chain amino acids (BCAAs), have important regulatory roles in protein synthesis. Recently studies revealed that BCAAs protect against ischemia/reperfusion (I/R) injury. We studied the signaling pathway and mitochondrial function affecting a cardiac preconditioning of BCAAs.Main methods: An in vivo model of I/R injury was tested in control, mTOR +/+ , and mTOR +/-. Mice were randomly assigned to receive BCAAs, rapamycin, or BCAAs + rapamycin. Furthermore, isolated cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…[26] Previously, we demonstrated that BCAAs show cardioprotective effects via the mTOR signaling pathway. [12] In this study, Leu reduced infarct size in wild-type mice, but not in mTOR +/− mice. Therefore, this result indicates that Leu is the key amino acid that stimulates mTOR activity and protects the heart from I/R injury.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…[26] Previously, we demonstrated that BCAAs show cardioprotective effects via the mTOR signaling pathway. [12] In this study, Leu reduced infarct size in wild-type mice, but not in mTOR +/− mice. Therefore, this result indicates that Leu is the key amino acid that stimulates mTOR activity and protects the heart from I/R injury.…”
Section: Discussionmentioning
confidence: 46%
“…[9] [10] [11] Recently, we showed the cardiac preconditioning effect of branched-chain amino acid (BCAA) treatment on I/R injury in mice, resulting from increased mammalian target of rapamycin (mTOR) activity and improved mitochondrial function. [12] Among BCAAs, leucine (Leu) can activate mTOR kinase, thereby leading to the phosphorylation of p70S6 kinase and increasing the phosphorylation of serine residues in insulin receptor substrate-1 [13], which inhibits insulin signaling and insulin-stimulated glucose transport in muscles and fats. However, whether Leu has cardioprotective effects on diabetic hearts is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were blocked in 20 mM Tris-buffered saline (TBS) plus Tween (0.1%) containing 2% skim milk and incubated with monoclonal primary antibodies (RYR1 (D4E1), #8153, Cell Signaling Technology, Danvers, MA, USA) overnight at 4°C. Immunolabeled blots were visualized using horseradish peroxidase-conjugated secondary antibodies (Santa Cruz Biotechnology, Dallas, TX, USA) and visualized using an enhanced chemiluminescence reagent (Bio-Rad Laboratories) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most effective intervention for acute myocardial infarction is timely revascularization (1)(2)(3). However, re-establishing blood to ischemic areas yields additional myocardial damage including inflammation, apoptosis and autophagy, which is known as myocardial ischemia/reperfusion (I/R) injury (MIRI) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The most effective intervention for acute myocardial infarction is timely revascularization (1)(2)(3). However, re-establishing blood to ischemic areas yields additional myocardial damage including inflammation, apoptosis and autophagy, which is known as myocardial ischemia/reperfusion (I/R) injury (MIRI) (1)(2)(3). The pathophysiological mechanism of MIRI is complex and numerous studies have confirmed that endoplasmic reticulum (ER) stress (ERS)-induced apoptosis serves important roles in the progression of MIRI (4,5).…”
Section: Introductionmentioning
confidence: 99%